Inspirational Intuition – A new controlling approach to moderate the intuitive imagination of knowledge - Jochem Müller (CARF Luzern 2021: Controlling. Accounting&Audit. Risk&Compliance. Finanzen., 2021)
This extended abstract shows the importance of human intuition in the context of creating new knowledge. In particular, inspirational intuition plays an important role. In contrast to Daniel Kahneman's fast, intuitive and routine decision-making in terms of a System 1 (Kahneman 2011, pp. 19 ff.), inspirational intuition is shown to be a slow, incubational, and illuminative force. As a System 3, it forms an important core human capability to enable unprecedented knowledge with the help of original intuitions. The scientific paper shows the development of a questionnaire to quantify inspirational intuition. With the help of a principal component analysis, central influencing factors of intuitive competence are elaborated and made more accessible for companies. Inspirational intuition supports the controller in his new role as Change Agent and Crea Scout. The design of forward-looking innovation processes is becoming a decisive factor for success. Intuitive knowledge generation retains its unique significance, especially in the age of artificial intelligence. – – Diese erweiterte Zusammenfassung zeigt die Bedeutung der menschlichen Intuition im Zusammenhang mit der Schaffung neuen Wissens. Insbesondere die inspirierende Intuition spielt dabei eine wichtige Rolle. Im Gegensatz zu Daniel Kahnemans schneller, intuitiver und routinemäßiger Entscheidungsfindung im Sinne eines Systems 1 (Kahneman 2011, S. 19 ff.) wird gezeigt, dass die inspirierende Intuition eine langsame, inkubatorische und erhellende Kraft ist. Als System 3 bildet sie eine wichtige Kernfähigkeit des Menschen, um mit Hilfe ursprünglicher Intuitionen ungeahntes Wissen zu ermöglichen. Die wissenschaftliche Arbeit zeigt die Entwicklung eines Fragebogens zur Quantifizierung der inspirierenden Intuition. Mit Hilfe einer Hauptkomponentenanalyse werden zentrale Einflussfaktoren der intuitiven Kompetenz herausgearbeitet und für Unternehmen zugänglich gemacht. Inspirierende Intuition unterstützt den Controller in seiner neuen Rolle als Change Agent und Crea Scout. Die Gestaltung von zukunftsweisenden Innovationsprozessen wird zum entscheidenden Erfolgsfaktor. Intuitive Wissensgenerierung behält gerade im Zeitalter der künstlichen Intelligenz ihre einzigartige Bedeutung.
Keywords: O; A; 330; Inspiration; Intuition; Imagination; Knowledge; Controlling